2017
DOI: 10.1128/jcm.00169-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sensitivity and Specificity Performance of Elecsys HTLV-I/II Assay in a Multicenter Study in Europe and Japan

Abstract: Screening of blood for human T-cell lymphotropic virus type 1 and type 2 (HTLV-1 and -2, respectively) is important to diagnose and prevent infection and ensure the safety of blood supplies. The Elecsys HTLV-I/II assay is a newly developed, electrochemiluminescence screening assay for the detection of HTLV-1/2 infection. The sensitivity and specificity of the Elecsys HTLV-I/II assay were determined using well-characterized HTLV-1/2-positive serum and plasma samples and routine diagnostic and blood donor sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
(26 reference statements)
1
10
0
7
Order By: Relevance
“…These findings correspond well with those reports from the prior multicenter study with the same anti‐HTLV assay . In the previous study, clinical sensitivity of Elecsys HTLV‐I/II was demonstrated at 100% (n = 1149) using clinical specimens from Japan, the United States, Europe, and the Middle East.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings correspond well with those reports from the prior multicenter study with the same anti‐HTLV assay . In the previous study, clinical sensitivity of Elecsys HTLV‐I/II was demonstrated at 100% (n = 1149) using clinical specimens from Japan, the United States, Europe, and the Middle East.…”
Section: Discussionsupporting
confidence: 91%
“…These findings correspond well with those reports from the prior multicenter study with the same anti-HTLV assay. 10 In the previous study, clinical sensitivity of Elecsys HTLV-I/II was demonstrated at 100% (n = 1149) using clinical specimens from Japan, the United States, Europe, and the Middle East. The clinical specificity was 99.95% (n = 11 575) from blood donors and 99.83% (n = 2399) from routine diagnostic samples, including pregnancies and specimens requested for hepatitis, HIV, HSV, EBV, and rubella virus testing.…”
Section: Discussionmentioning
confidence: 94%
“…CLIA (Qiu et al, 2008), and ECLIA (Laperche et al, 2017). These assays are available in Japan because they are capable of processing large numbers of samples in a relatively short time.…”
Section: Assays For Htlv-1 Antibody Screeningmentioning
confidence: 99%
“…Human T-lymphotropic virus screening is performed routinely in our center in all the SOT candidates. AVIOQ ® HTLV-I/II Microelisa System, a highly specific and sensitive assay, 3 was the serologic test used in our study. False positivity is unlikely as the specificity of the assay is 99.95%.…”
Section: Screening Of Human T-lymphotropic Virus Among Solid Organ Trmentioning
confidence: 99%